An empirical investigation into Malaysia’s economic growth : income inequality and foreign direct investment / Azfar Hilmi bin Baharudin - Baharudin, Azfar Hilmi (2013)

(untitled)
This paper embarks on an extensive empirical investigation on economic growth for Malaysia, with attention on income inequality, foreign direct investment, financial development and trade. OLS procedure was employed in experimenting with different proxies for financial development and finds robust positive relationship between growth and financial development. FDI and trade are also found to be significant contributors to Malaysia’s economic development. Income inequality however, does not seem to exhibit meaningful statistical relationship. These findings are generally mirrored in the three cointegrating regressions employed namely FMOLS, CCR and DOLS procedures. The orders of integration for variables used have been demonstrated to be governed such that a long-run relationship prevails. Additionally, bivariate long-run relationship is also found between growth and FDI, income inequality and FDI as well as financial development and FDI. In short-run horizon, statistical significance of financial development and trade breaks down, and the effects of income inequality and trade reverses. Thus effectively, FDI is the only variable considered in this paper to have significant implications on growth in the short-and long-run horizon. This paper also finds evidence of unidirectional causality that runs from income inequality to growth and income inequality to FDI. Bidirectional causality is detected between trade and economic growth. Another experimental consideration fails to reveal any moderating effects stemming from financial development, trade and FDI on the equity-efficiency nexus.